The verbal realizations of the perfect aspect in Canadian English - Lopes, Thais Lima; Martins, Adriana Leitão (Estudos Linguísticos (São Paulo. 1978), 2025)
The perfect aspect associated with the present conveys the idea that a situation started or occurred in the past and continues or has effects in the present (universal perfect – UP x existential perfect – EP). This study aimed to investigate the morphological realizations of UP and EP associated with the present in Canadian English, and comparatively analyze these realizations. An experimental study was developed including a cloze test and a decision task. The hypotheses were that, apart from the Present Perfect, Canadian English uses (i) other morphological forms to express UP and EP associated with the present, and (ii) these forms are different for each type of perfect. These hypotheses were supported, as the results showed that, apart from Present Perfect, different forms are used for UP and EP.